Tobacco cessation among smokers under substance use treatment for alcohol and/or cannabis: study protocol and pilot study - Ariadna Feliu; Esteve Fernández; Yolanda Castellano; Marta Enríquez; Judith Saura; Carmen Cabezas; Joan Colom; Josep M. Suelves; Margarida Pla; Mar Parejo; Sílvia Mondon; Pablo Barrio; et al. (Addiction Science & Clinical Practice, 2022)
Abstract Background Approximately 80% of people with a substance use disorder (SUD) are smokers. Starting SUD treatment offers the opportunity to also quit smoking. The ACT-ATAC project aims to identify the predictors associated with smoking cessation among persons treated for alcohol and/or cannabis use disorder in Barcelona. This manuscript reports its methodology and the experience of carrying it out during the COVID-19 pandemic. Methods Mixed methods project with three substudies. Substudy 1 (S1) comprises heterogeneous discussion groups among clinicians. S2 has two prospective cohorts composed of smokers under treatment for alcohol and/or cannabis use disorder and the clinicians in charge of these patients. Participating smokers will be followed for 12 months and interviewed about their substance use and the tobacco cessation services received using the Spanish version of the users’ Knowledge, Attitudes, and Services (S-KAS) scale. The clinicians will be asked about their self-reported practices in smoking cessation using the Knowledge, Attitudes, and Practices (S-KAP) scale. S3 comprises heterogeneous discussion groups with smokers. Data will be triangulated using qualitative and quantitative analyses. To facilitate the recruitment process, the researchers have introduced several strategies (design clear protocols, set monthly online meetings, extend the project, provide gift cards, etc.). Discussion The results of S1 were used to develop the questionnaires. S2 required some adjustments due to the COVID-19 pandemic, particularly the follow-up interviews being conducted by phone instead of face-to-face, and the recruitment rhythm was lower than expected. Recruitment will last until reaching at least 200–250 users. The fieldwork could not have been possible without the collaboration of the ACT-ATAC team and the introduction of several strategies. Trial registration The ACT-ATAC project has been successfully registered at Clinicaltrials.gov [NCT04841655].